2019
DOI: 10.12957/childphilo.2019.46229
|View full text |Cite
|
Sign up to set email alerts
|

teaching critical thinking and metacognitive skills through philosophical enquiry. A practitioner's report on experiments in the classroom.

Abstract: Although expert consensus states that critical thinking (CT) is essential to enquiry, it doesn’t necessarily follow that by practicing enquiry children are developing CT skills. Philosophy with children programmes around the world aim to develop CT dispositions and skills through a community of enquiry, and this study compared the impact of the explicit teaching of CT skills during an enquiry, to The Philosophy Foundation's philosophical enquiry (PhiE) method alone (which had no explicit teaching of CT skills)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In controlled studies by Trickey and Topping, collaborative philosophical dialogue has been associated with better cognitive and metacognitive skills in the intervention group (Topping & Trickey 2007b, 2007aTrickey & Topping 2004, 2007. This is consistent with Worley's argument that PhiE fosters metacognitive skills (Worley 2018) and with research carried out in 2019 by TPF and King's into the teaching of critical thinking and metacognitive skills through PhiE (Worley & Worley 2019). This research showed a 63% increase in the intervention groups' successful use of critical thinking skills and metacognition.…”
Section: Pupilssupporting
confidence: 81%
See 1 more Smart Citation
“…In controlled studies by Trickey and Topping, collaborative philosophical dialogue has been associated with better cognitive and metacognitive skills in the intervention group (Topping & Trickey 2007b, 2007aTrickey & Topping 2004, 2007. This is consistent with Worley's argument that PhiE fosters metacognitive skills (Worley 2018) and with research carried out in 2019 by TPF and King's into the teaching of critical thinking and metacognitive skills through PhiE (Worley & Worley 2019). This research showed a 63% increase in the intervention groups' successful use of critical thinking skills and metacognition.…”
Section: Pupilssupporting
confidence: 81%
“…That cannot happen when the facilitator, who is not a peer, is too present in the shaping of the conversation-if only because the participants will defer to the facilitator's judgements, instead of standing by their own. PhiE operationalises a kind of neutrality with four basic techniques for responding to what different interlocutors say: echoing, opening up, anchoring and if-ing (Worley 2010(Worley , 2021Worley & Worley 2019). These techniques apply to answers or responses that participants offer to the introductory task question.…”
Section: Techniques For Neutralitymentioning
confidence: 99%
“…The organisation chosen was The Philosophy Foundation in London (UK) (for the approach of this organisation and our adaption of it see, e.g. Schaffalitzky 2021, p. 8;Worley 2011). Based on this collaboration, we started establishing a practice involving trained facilitators, who were a mixture of philosophy students and staff.…”
Section: Initial Aims Of the Programmementioning
confidence: 99%
“…Topping & Trickey, 2007;Millett & Tapper, 2012, pp. 8-10;Fair et al, 2015;Säre et al, 2016;Worley & Worley, 2019).…”
Section: Philosophical Dialogue In Educational Research On Dialogic Teachingmentioning
confidence: 99%